FORMATION OF SYSTEMATIC KNOWLEDGE IN SCIENCE STUDENTS IN HIGHER EDUCATION - Safonova,; Khudyakova,; Voronkova,; Bolbukh,; Kaiser, (Revista Inclusiones, 2020)
The study deals with the main issues of developing systematic knowledge in students within higher education and provides possible solutions. A scheme of systematic approach stages is proposed. Particular attention is given to examples from pedagogical practice.